List of well-being indicators - Claudia Kettner; Angela Köppl; Sigrid Stagl (WWWforEurope, 2012)
This milestone presents a pool of available indicators and indicator systems which go beyond the narrow concepts of national economic accounts as well as a structuring of the indicators and indices according to central areas of well-being. The milestone builds the basis for Task 202.2, where a subset of indicators will be selected based on different theoretical frameworks, e.g. services / functionings, needs. Some of the indicators will be included in the macro-economic 3 models in order to account for key dimensions of sustainability.
Keywords: D63; E01; I32; 330; Sozialer Indikator; Makroökonomisches Modell